Examining Obesity and the Effects of Weight Bias in Western Medicine - Dickerson, Katherine (My University, 2024)
The increase in the global prevalence of obesity has become a major issue in medicine. Obesity is a complex and serious disease, often resulting from an interplay between physiology, environment, and lifestyle choices. As the rise of obesity continues, so does the pervasiveness of weight bias. Stigmas surrounding weight and weight-based discrimination have a widespread prevalence in the Western healthcare setting and among healthcare providers and students. Weight bias leads to many adverse health consequences, including worsening a patient’s health and negatively impacting their experiences in healthcare. Views on body image, over-idealization of thinness in Western society, and the lack of education and training have perpetuated worsening stigma and biases towards individuals who are overweight or have obesity. Stereotypes and discrimination based on weight do not motivate individuals to lose weight and instead contribute to worse health outcomes. Addressing biases and eliminating harmful stereotypes of weight stigma is crucial for creating a culture of medicine that promotes respect, inclusivity, and empowers patients with the ability to make changes that better their health.